2010
DOI: 10.1155/2010/284840
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transfer into the Lung by Nanoparticle Dextran-Spermine/Plasmid DNA Complexes

Abstract: A novel cationic polymer, dextran-spermine (D-SPM), has been found to mediate gene expression in a wide variety of cell lines and in vivo through systemic delivery. Here, we extended the observations by determining the optimal conditions for gene expression of D-SPM/plasmid DNA (D-SPM/pDNA) in cell lines and in the lungs of BALB/c mice via instillation delivery. In vitro studies showed that D-SPM could partially protect pDNA from degradation by nuclease and exhibited optimal gene transfer efficiency at D-SPM t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 56 publications
(57 reference statements)
2
30
0
Order By: Relevance
“…We have reported that the dextran-spermine based polycations have been found to be highly effective as nonviral vectors in transfecting many different cells in vitro. [11][12][13][14][15][16][17] Our recent study also demonstrated that electrospun poly (glycolic acid) (PGA)/ collagen nanofibers significantly enhanced cell adhesion compared with PGA/collagen microfibers. 18 Based on these results, the present study aims to fabricate a tissue-like 3D transgene cell construct for use as a therapeutic cell-based gene delivery system or as an in vitro model system for testing genetic manipulations to understand the effects of gene expression on tissue development.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that the dextran-spermine based polycations have been found to be highly effective as nonviral vectors in transfecting many different cells in vitro. [11][12][13][14][15][16][17] Our recent study also demonstrated that electrospun poly (glycolic acid) (PGA)/ collagen nanofibers significantly enhanced cell adhesion compared with PGA/collagen microfibers. 18 Based on these results, the present study aims to fabricate a tissue-like 3D transgene cell construct for use as a therapeutic cell-based gene delivery system or as an in vitro model system for testing genetic manipulations to understand the effects of gene expression on tissue development.…”
Section: Introductionmentioning
confidence: 99%
“…Dextran is neutral at physiological pH and therefore does not effectively bind DNA, thus cationic molecules or polymers are commonly incorporated into dextran NPs to improve their effectiveness in gene therapy applications. Dextran NPs incorporating cationic methacrylate monomers and spermine (a tetravalent amine) have been used for the delivery of plasmid DNA in vitro (COS7 and HEK293) and in vivo (trachea and lung, and colorectal cancer) [157159]. Other dextran NPs conjugated to cationic polymers such as PEI or poly-β-amino ester also show high binding efficiency to plasmid DNA, as well as the ability to escape endosomes [160, 161].…”
Section: Nps For Retinal Gene Therapymentioning
confidence: 99%
“…A novel cationic polymer, dextran-spermine, has been found to mediate gene expression in a wide variety of cell lines and in vivo through systemic delivery of plasmid DNA, partially protected from degradation by nuclease. This exhibited optimal gene transfer effi ciency [ 41 ].…”
Section: Dextranmentioning
confidence: 99%